Economic dependence and political change in Algeria : 1962-1992 - Nasser, Youcef (Lambert Academic Publishing, 2009)
This study introduces the theory of economic dependence and applies the standard indicators, developed by economists in the past five decades, to the Algerian economic situation since its independence from France in 1962. It shows how the economic dependence in Algeria contributed to its political dependence, and to political changes that deviated from historical national norms. This is especially demonstrated in the case of the recent Algerian crisis, in which over 100,000 lives have been lost. This analytical perspective argues that Algeria s current economic problems are primarily caused by Algeria s economic dependence on France and other Western capitalist countries. The internal political instability that has subsequently occurred is a direct result of the imbalance that exists in its foreign trade and international relations. A factual basis is presented to show how Algeria s political malaise is intimately associated with its external economic dependence